Interleukin-33, an interleukin-1 like cytokine accelerates cell migration in IEC-6 cells - Islam, Md Shafiqul; Hori, Masatoshi; Ozaki, Hiroshi (Asian Journal of Medical and Biological Research, 2017)
Interlukin-33 (IL-33) is a novel cytokine of the IL-1 superfamily that is expressed mainly in stromal cells, such as epithelial and endothelial cells. It is believed to be involved in inflammation and carcinogenesis. Recently we have reported that IL-33 is up regulated in azoxymethane-dextran sulfate sodium salt (AOM/DSS)- induced in colitis in mice. In this study we have investigated the biological activity of IL-33 in cells migration in IEC-6 epithelial cells. Our wound healing assay demonstrated that IL-33 significantly enhanced cell migration towards the wound edges compared with the untreated control cells. Trans-well migration assay in presence of cells culture and wound stimulation in the lower chamber, IL-33 exhibited significant chemoattractant activity for the cells migration. On the other hand, in absence of cells culture and wound stimulation in the lower chamber, IL-33 neither produced remarkable chemokine, nor chemoattractant activity for the cells migration. These findings indicate that IL-33 interacts with wound-stimulated soluble cellular product(s) in the lower chamber to accelerate cell migration. Asian J. Med. Biol. Res. December 2016, 2(4): 577-581